2000
DOI: 10.1007/s002800000145
|View full text |Cite
|
Sign up to set email alerts
|

The role of caspase family protease, caspase-3 on cisplatin-induced apoptosis in cisplatin-resistant A431 cell line

Abstract: These findings suggest that caspase-3 may mediate apoptosis induced by CDDP, and its induction could represent a novel approach to the effective treatment of malignant tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Although cisplatin-induced apoptosis occurs through caspasedependent and caspase-independent mechanisms (Gonzalez et al, 2001), caspase-dependent apoptosis has been reported for the A431 cell line (Mese et al, 2000;Sawada et al, 2003). We examined the involvement of caspases during Titanocene Y-induced apoptosis in A431 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although cisplatin-induced apoptosis occurs through caspasedependent and caspase-independent mechanisms (Gonzalez et al, 2001), caspase-dependent apoptosis has been reported for the A431 cell line (Mese et al, 2000;Sawada et al, 2003). We examined the involvement of caspases during Titanocene Y-induced apoptosis in A431 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, cisplatin directly binds DNA by forming intra-and interstrand crosslinks which cause the DNA to unwind and bind other proteins, thus preventing DNA repair. Like etoposide, cisplatin-induced apoptosis has been found to invoke a caspase-3 mediated pathway (Mese et al, 2000). The 293 HEK stable cell lines were exposed to 10 lg/mL cisplatin with subsequent data analysis at 24 h intervals.…”
Section: Chemical Exposure Of Stably Transfected 293 Hek Cellsmentioning
confidence: 99%
“…Amphotericin B-induced apoptosis as noted by the nucleosome ELISA was apparently not dependent on caspase-3 activation. Caspase-3 activity measurements of cisplatin-induced apoptosis 11 were valuable as the cisplatin effect on nucleosome fragmentation was less pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Like most chemotherapeutic agents, cisplatin and carboplatin exert their action by inducing apoptosis, 9,10 probably mediated through caspase-3 activation. [11][12][13] To explore if enhanced potassium efflux could affect cisplatin and/or carboplatin induction of apoptosis and cytotoxicity we used amphotericin B as K ϩ ionophore. Amphotericin B is a polyene anti-fungal antibiotic known to potentiate cisplatin cytotoxicity in normal and cisplatinresistant cells, 14,15 by inducing cell membrane pores leading to potassium efflux.…”
mentioning
confidence: 99%